Comparison of postoperative pain after open and endoscopic carpal tunnel release: A randomized controlled study - (:unkn) unknown (MEDKNOW PUBLICATIONS & MEDIA PVT LTD, 2016)
Background: Results of open and endoscopic carpal tunnel surgery were compared with many studies done previously. To the best of our knowledge, difference in pain after endoscopic carpal tunnel release (ECTR) and open carpal tunnel release (OCTR) has not been objectively documented in literature. The aim of the study was to compare the pain intensity in the early postoperative period in patients undergoing OCTR versus those undergoing ECTR. Materials and Methods: Fifty patients diagnosed with carpal tunnel syndrome were randomized into two groups using random number generator software (Research Randomizer, version 3.0); endoscopic surgery group [(21 female, 1 male; mean age 49 years (range 31u64 years)] and open surgery group [(25 female, 3 male; mean age 45.1 years (range 29u68 years)] and received carpal tunnel release. Surgery was performed under regional intravenous anesthesia. The patients' pain level was assessed at the 1(st), 2(nd), 4(th), and 24(th) postoperative hours using a visual analog scale (VAS) score. Results: Mean age, gender and duration of symptoms were found similar for both groups. Boston functional scores were improved for both groups (P 0.001, P 0.001). Pain assessment at the postoperative 1(st), 2(nd), 4(th) and 24(th) hours revealed significantly low VAS scores in the endoscopic surgery group (P = 0.003, P 0.001, P 0.001, P 0.001). Need for analgesic medication was significantly lower in the endoscopic surgery group (P 0.001). Conclusion: Endoscopic carpal tunnel surgery is an effective treatment method in carpal tunnel release vis-a-vis postoperative pain relief.
Keywords: Carpal tunnel syndrome; endoscopic surgery; open surgery; wrist; postoperative painMeSH terms; CONTROLLED-TRIALS; SURGERY; OUTCOMES